Performance evaluation of laboratory scale up-flow constructed wetlands with different designs and emergent plants. - Soon-An, Ong; Uchiyama, Katsuhiro; Inadama, Daisuke; Ishida, Yuji; Yamagiwa, Kazuaki (Elsevier Ltd, 2011)
Link to publisher’s homepage at http://www.elsevier.com/